Perception and trust influence acceptance for black bears more than bear density or conflicts - Siemer, William F.; Lauber, T. Bruce; Stedman, Richard C.; Hurst, Jeremy E.; Sun, Catherine C.; Fuller, Angela K.; Hollingshead, Nicholas A.; Belant, Jerrold L.; Kellner, Kenneth F. (Frontiers in Conservation Science, 2023)
To sustain black bear populations, wildlife managers must understand the coupled socio-ecological systems that influence acceptance capacity for bears. We spatially matched datasets from three sources in New York State: human-bear conflict records (2006–2018), local black bear density estimates based on 2017–2018 data, and a 2018 property owner survey (n=10,028, 40% response). We used structural equation modeling to test hypothesized relationships between human-bear conflict, bear density, and psychological variables. The final model was a good fit for the data (CFI=0.931; RMSEA=0.053) and explained 57% of the variance in acceptance. The effect of bear population density on acceptance capacity for bears was relatively small and was mediated by a third variable: perceived (psychological) distance from the effects of human-bear interactions. The variables that exerted a direct effect on acceptance were bear-related benefits, bear-related risks, proximity to effects of bears, and being a hunter. Bear-related benefits had a greater effect on acceptance than bear-related risks. Perceived proximity to effects of bears was affected by bear density, but also was affected by social trust. Increased social trust had nearly the same effect on perceived proximity as decreased bear density. Social trust had the greatest indirect effect on acceptance of any variable in the model. Findings suggest wildlife agencies could maintain public acceptance for black bears through an integrated approach that combines actions to address bear-related perceptions and social trust along with active management of bear populations.